Методологія визначення руйнівних навантажень на великогабаритні тонкостінні конструкції з урахуванням результатів неруйнівних випробувань - Marchuk, M. V.; Марчук М. В.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів; Sirenko, V. M.; Сіренко В. М.; Державне підприємство «Конструкторське бюро «Південне» ім. М. К. Янгеля», Дніпро; Drobenko, B. D.; Дробенко Б. Д.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2020)
The basics of the methodology for determining the actual destructive loads on large-scale thin-walled structures with a complex shape of the front surfaces under geometrically nonlinear stress-plastic deformation due to internal pressure taking into account the results of non-destructive experimental tests are proposed.  Cite as: M. V. Marchuk, V. M. Sirenko, B.D. Drobenko, “Methodology for determination of destructive loads on large-scale thin-walled structures taking into account the results of non-destructive tests,” Prykl. Probl. Mekh. Mat., Issue 18, 133–138 (2020) (in Ukrainian), https://doi.org/10.15407/apmm2020.18.133-138